Effect of host and non‐host crops on Plasmodiophora brassicae resting spore concentrations and clubroot of canola. (19th February 2015) - Hwang, S. F.; Ahmed, H. U.; Zhou, Q.; Turnbull, G. D.; Strelkov, S. E.; Gossen, B. D.; Peng, G.
Abstract : Plasmodiophora brassicae, causal agent of clubroot of crucifers, poses a serious threat to Canadian canola production. The effects of fallow (F) periods and bait crops (clubroot‐susceptible canola (B) and perennial ryegrass (R)) on clubroot severity and P. brassicae resting spore populations were evaluated in five sequences: R–B, B–R, R–F, B–F and F–F. Both host and non‐host bait crops reduced clubroot severity in a subsequent crop of a susceptible canola cultivar compared with fallow. Resting spore and P. brassicae DNA concentrations decreased in all treatments, but were lowest for the R–B and B–R bait crop sequences. In addition, two studies were conducted in mini‐plots under field conditions to assess the effect of rotation of susceptible or resistant canola cultivars on clubroot severity and P. brassicae resting spore populations. One study included three crops of susceptible canola compared with a 2‐year break of oat–pea, barley–pea, wheat–wheat or fallow–fallow. The other study assessed three crops of resistant canola, two crops of resistant canola with a 1‐year break, one crop of resistant canola and a 2‐year break, and a 3‐year break with barley followed by a susceptible canola. The rotations that included non‐host crops of barley, pea or oat reduced clubroot severity and resting spore concentrations, and increased yield, compared with continuous cropping of either resistant or susceptible canola. Growing of a susceptible canola cultivar contributed 23–250‐fold greater gall mass compared with resistant cultivars.